Square Root 1

Function: Square RootIdentify the correct equation for each graph y=½√x y=-√x y=x ^{-½}y=x ^{½}y=½√x y=-√x y=x ^{-½}y=x ^{½}y=√(x+1)+1 y=√(x+1)-1 y=√(x-1)+1 y=√(x-1)-1 y=√(x+1)+1 y=√(x+1)-1 y=√(x-1)+1 y=√(x-1)-1 y=√(x+1)+1 y=√(x+1)-1 y=√(x-1)+1 y=√(x-1)-1 y=√(x+1)+1 y=√(x+1)-1 y=√(x-1)+1 y=√(x-1)-1 y=½√x y=√(½x) y=2x ^{-½}y=2x ^{½}y=3√x y=√(⅓x) y=√(3x) y=⅓√x y=3√x y=√(⅓x) y=√(3x) y=⅓√x 3√x √(⅓x) √(3x) ⅓√x |

Students who took this test also took :

Created with That Quiz —
where a math practice test is always one click away.